Transforaminal lumbar interbody fusion with expandable cages: Radiological and clinical results of banana-shaped and straight implants - Tjark Tassemeier; Marcel Haversath; Marcus Jäger (Journal of Craniovertebral Junction and Spine, 2018)
Purpose: Expandable titanium transforaminal lumbar interbody fusion (TLIF) devices are a relatively new group of implants allowing restoration of lumbar lordosis (LL) and thus improvement of sagittal alignment. The purpose of our study is to compare clinical and radiological results of two different expandable TLIF devices. Materials and Methods: In a retrospective study, patients who underwent TLIF surgery with a banana-shaped or straight TLIF cage in our spine center were analyzed. Primary outcome was change of disc height (DH), segmental lordosis angle (SLA), and lumbar lordotic angle (LLA). Moreover, basic patients parameters and cage subsidence were evaluated. Results: Sixty-one patients were studied (33 banana-shaped and 28 straight cages). DH changed in the banana group from 4.8 mm (standard deviation SD 2.5) to 10.4 (SD 2.4) and in the straight cage group from 6.2 mm (SD 2.5) to 9.6 mm (SD 1.7). The difference was statistically significant (P = 0.03). In addition, SLA correction was higher in the banana group with 5.8° (SD 5.0)–3.7° (SD 3.6), but not significant. LLA improved in the straight group with 5.2 (SD 6.4) compared to 3.7° (SD 5.8) in the banana group. We found subsidence in four patients (6.6%) in the banana-shaped group and nine cases (14.8%) in the other group. Conclusions: Expandable titanium implants show similar improvements in restoring segmental and global lordosis. Banana-shaped expandable cages offer higher potency restoring the intervertebral DH and show less rates of subsidence compared to straight expandable cages.